PERSEPSI PENGUNJUNG TAMAN TERHADAP KENYAMANAN FASILITAS DI HUTAN KOTA PATRIOT BINA BANGSA BEKASI SEBAGAI RUANG PUBLIK - Santosa, Alfa Akbar; Melanira, Astria (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
Interest and awareness to use the park is still underutilized by the people in Bekasi City asa public space, especially the Patriot Bina Bangsa Bekasi City Forest as the largest park in thecity of Bekasi. Is it due to the lack of garden comfort, due to unfavorable conditions or caused byother factors. Therefore, the author examines whether the interest and awareness of the people ofBekasi City to visit the park is caused by a lack of comfort. It is necessary to research theperception of park visitors on the convenience of facilities in the Patriot Bina Bangsa Bekasi CityForest. The expected results from the visitor's perception can answer whether the park facilitiesin the Patriot Bina Bangsa Bekasi City Forest are comfortable to visit as public spaces.